INDIVIDUAL DISCIPLINE WITH PERSONAL CONTENT ORGANIZE WORK - Mannabov Abduxamid Abdimajitovich (American Journals Publishing, 2023)
It is intended by the command, governing bodies, commander and their deputies (service chiefs) to know deeply the spirituality, level of knowledge, family situation and behavior, characteristics, actions and discipline in the community, and their specifics.The article discusses the organization of individual educational work with personal content.
Keywords: Individual discipline, one-order conversation, one-order approach, observation, passing documents, conversation, tempolandament, studying individual-psychological characteristics of an individual.